The Bahamas : Financial Sector Assessment Program-Technical Note on Financial Stability and Stress Testing. (IMF Staff Country Reports; Country Report ;, 2019)
Macrofinancial risks stem from the economy's vulnerability to external shocks to tourism and real estate investment, exposure to frequent and severe hurricanes, and a small and illiquid real estate market. Stress tests reveal the overall banking system is resilient to a range of adverse scenarios given large aggregate capital and liquidity buffers. Some domestic banks and the two largest credit unions are more vulnerable to asset quality shocks and tail risk conditions. Asset quality and profitability are key determinants of financial institutions' resilience to adverse shocks. Liquidity, market, sovereign and financial contagion risks are low. The offshore banking sector is not a source of traditional banking risks.